Leverage pro-cyclicality and securitization in US banking - Beccalli, Elena; Boitani, Andrea; Di Giuliantonio, Sonia (Journal of Financial Intermediation, 2015)
This paper investigates the role of off-balance sheet securitization on US bank leverage pro-cyclicality. Effective leverage (taking into account off-balance sheet securitization) is especially relevant for the US, where GAAP accounting rules for securitization allowed until 2009 a underestimation of on balance sheet items. Over 2001–2010, we document that US BHCs which are more involved in securitization have a more pro-cyclical leverage. We also show that in the pre-crisis period securitization dominates the business model in determining the leverage pro-cyclicality to the point that even commercial banks highly involved in securitization had a pro-cyclical behavior. We document that the period-long relation between securitization and capital ratios was week. The effect on leverage pro-cyclicality of the 2004 changes in regulation (the new SEC net capital rule and the exemption from the FASB directive on consolidation of SPVs) was absent for investment banks, and mixed for commercial banks highly involved in securitization. The evidence of this paper supports the view of the Basel III committee that macro-prudential regulation must include constraints on effective leverage.